If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 24 = 4x + 24 Reorder the terms: 24 + 3x = 4x + 24 Reorder the terms: 24 + 3x = 24 + 4x Add '-24' to each side of the equation. 24 + -24 + 3x = 24 + -24 + 4x Combine like terms: 24 + -24 = 0 0 + 3x = 24 + -24 + 4x 3x = 24 + -24 + 4x Combine like terms: 24 + -24 = 0 3x = 0 + 4x 3x = 4x Solving 3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = 4x + -4x Combine like terms: 3x + -4x = -1x -1x = 4x + -4x Combine like terms: 4x + -4x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 3x-2y+3z=12 | | -9y=12x | | X^3+x=27000 | | -3(x+5)+6(3x-4)=7(x+3)-(2x+6) | | -3(x+5)+6(3x-4)=7(x+3)-(2x+6) | | 7-4x/5=19 | | p^2-3*p=1 | | 7-4/5x=19 | | 7x+1=x+31 | | sqrt(x-1)+sqrt(x+3)+2*sqrt((x-1)*(x+3))=4-2x | | 2.50(1.50x)=26.50 | | 5X+3X+2Y=52 | | 0.50x-30(50+x)=-0.18(50) | | 6y-12-4y+9=0 | | 8(x+2)-3(3x-1)=4x+4 | | -12+(-3a)=0 | | -2x+9(6-(-2))=8x | | 3x+2x=750 | | 3/9=x/4x-7 | | 9/3=4x-7/x | | (9-z)(2z-7)=0 | | 1/4(160)-1/6(160)= | | (y-5)-(y+7)=7y | | 1/25x=14 | | 5(r+9)-(1-r)=1 | | 1/5c=145 | | 11+18x=20+15x | | 1/4160-1/6160= | | 4(2x-7)=77 | | 2x+1+2=0 | | -65=11-2x | | 3x^3/√10-12 |